Identifying and understanding the historical extent of side channels on the Missouri River - Hook, Lisa (Kansas State University, 2011)
The US Army Corps of Engineers (USACE) has begun side channel restoration projects on the Missouri River as part of the Missouri River Recovery Program. The USACE acquires land on the Missouri River needed to develop fish and wildlife habitat. There is a need to prioritize which land to purchase on the Missouri River. High priority land would be areas that had side channels and can be constructed to restore ecosystems to a more natural state. Much of the river has since been dammed, straightened, and channelized starting heavily in the mid 1890’s, and historical side channels have been eliminated, leaving little information to guide USACE efforts to restore them. My thesis documents the historical distribution of side channels on the Missouri River between St. Louis and Kansas City and explores the relationships between side channel location and a variety of potential driving variables, including channel sinuosity, valley width, valley slope and the presence of large confluences. This is the first know study to document the historical extent of side channels on a major river system, and it is also the first to quantitatively explore driving variables of side channel formation. The historical analysis revealed abundant side channels in the late 1800’s, with a dramatic decline into the early 1920’s as engineering works on the river began in earnest. Results also show that high channel sinuosity and the presence of a large confluences are the two variables most correlated with side channel formation. Based on documented frequencies and locations of historical side channels, recommendations for specific side channel restoration opportunities are also highlighted.
Keywords: Side channels; Missouri River; Geography (0366)